التفريق بين الزوجين للغيبة في الفقه الإسلامي وفي قوانين دول مجلس التعاون الخليجي: دراسة فقهية مقارنة - القحطاني، حسين مبارك فارس (جامعة أم القرى, 2023)
من المسائل الجديرة بالبحث مسألة التفريق بين الزوجين لأجل غيبة الزوج، لارتباطه بحياة الناس في طلبهم للكسب وغيابهم لأجل ذلك عن أهليهم وأوطانهم، مع ما قد يطرأ من غياب قسري لكوارث عامة أو نظم قانونية في بعض البلدان. وهدف هذا البحث بيان اتجاهات الفقهاء في هذه المسألة مع توضيح ما أخذت به قوانين الأحوال الشخصية في دول الخليج العربي. وابتدأ الباحث بمقدمه، ثم عرف الغيبة وبين الخلاف وسببه في مشروعية التفريق بين الزوجين لأجلها، ثم وضح شروط هذه الفرقة، ثم أعقب ذلك بتوضيح نوع الفرقة الحاصلة بذلك، وبعد ذلك أورد ما أخذت به قوانين الأحوال الشخصية في دول الخليج، ثم ختم البحث بخاتمة تضمنت أهم النتائج والتوصيات. وكان من أهم التوصيات مراجعة قوانين الأحوال الشخصية في ظل المستجدات المعاصرة، وكذلك التوصية بالأخذ بأبعد الآجال التي وردت في تقدير مدة الغيبة. The issue of spouse separation due to the husband's absence is a topic deserving research due to its significant impact on people's lives, particularly in their pursuit of livelihood and the consequent separation from their families and homelands. This issue is also relevant to circumstances involving forced separations due to public calamities or legal systems in some countries. The primary objective of this research is to shed light on the perspectives of faqihs (jurists) regarding this matter and to elucidate the regulations governing personal status in the Arab Gulf States. The study commences with an introductory section, followed by the definition of absence and disagreements, along with an examination of their justifications for the legal separation of spouses. It also delves into the types of divisions that may result from such separations. Furthermore, the study outlines the provisions incorporated within the personal status laws of the Gulf States. In conclusion, the research encapsulates its key findings and recommendations. One of the noteworthy recommendations involves conducting a review of personal status laws in light of recent developments. Additionally, it is advised to consider extending the duration of allowable husband's absence when estimating separation length.
Keywords: الفقه الإسلامي -- المشكلات الأسرية -- مجلس التعاون الخليجي -- قانون الأحوال الشخصية -- الشريعة الإسلامية